Methane, carbon dioxide, and nitrous oxide emissions from two clear-water and two turbid-water urban ponds in Brussels (Belgium) - T. Bauduin; T. Bauduin; N. Gypens; A. V. Borges (Biogeosciences)
Shallow ponds can occur either in a clear-water state dominated by macrophytes or a turbid-water state dominated by phytoplankton, but it is unclear if and how these two alternative states affect the emission of greenhouse gases (GHGs) such as carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O) to the atmosphere. We measured the dissolved concentration of CO2, CH4, and N2O from which the diffusive air–water fluxes were computed, in four urban ponds in the city of Brussels (Belgium): two clear-water macrophyte-dominated ponds (Silex and Tenreuken), and two turbid-water phytoplankton-dominated ponds (Leybeek and Pêcheries) on 46 occasions over 2.5 years (between June 2021 and December 2023). Ebullitive CH4 fluxes were measured with bubble traps in the four ponds during deployments in spring, summer, and autumn, totalling 48 d of measurements. Measured ancillary variables included water temperature, oxygen saturation level ( %O2), concentrations of chlorophyll-a (Chl-a), total suspended matter (TSM), soluble reactive phosphorus (SRP), nitrite (NO<msubsup>2-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="cf5ab84666d459bfffb5030e23e4ac33"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-3785-2025-ie00001.svg" width="9pt" height="16pt" src="bg-22-3785-2025-ie00001.png"/></svg:svg>), nitrate (NO<msubsup>3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="ee54bb0fff66afdafaf51bed1fde360d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-3785-2025-ie00002.svg" width="9pt" height="16pt" src="bg-22-3785-2025-ie00002.png"/></svg:svg>), and ammonium (NH<msubsup>4+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="f1ca5762abf079d28af10bf21d382d4c"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-3785-2025-ie00003.svg" width="8pt" height="15pt" src="bg-22-3785-2025-ie00003.png"/></svg:svg>). The turbid-water and clear-water ponds did not differ significantly in terms of diffusive emissions of CO2 and N2O. Clear-water ponds exhibited higher values of ebullitive CH4 emissions compared to turbid-water ponds, most probably in relation to the delivery of organic matter from macrophytes to sediments, but the diffusive CH4 emissions were not significantly different between clear- and turbid-water ponds. Across seasons, CH4 emissions increased with water temperature in all four ponds, with ebullitive CH4 fluxes having a stronger dependence on water temperature (Q10) than diffusive CH4 fluxes. The temperature sensitivity of ebullitive CH4 fluxes decreased with increasing water depth, implying that shallow sediments would respond more strongly to warming (e.g. heat waves). Total annual CH4 emissions (diffusive + ebullitive) in CO2 equivalents equalled those of CO2 in turbid-water ponds and exceeded those of CO2 in clear-water ponds, while N2O emissions were negligible compared to the other two GHGs. Total annual GHG emissions in CO2 equivalents from all four ponds increased from 2022 to 2023 due to higher CO2 diffusive fluxes, likely driven by higher annual precipitation in 2023 compared to 2022 (leading putatively to higher inputs for organic or inorganic carbon from run-off), possibly in response to the intense El Niño event of 2023. The findings of this work suggest that it might be necessary to account for the presence of submerged macrophytes when extrapolating ebullitive CH4 fluxes in ponds at a larger scale (regional or global) (particularly if Chl-a is used as a descriptor), although it might be less critical for the extrapolation of diffusive CH4, CO2, and N2O fluxes.